2013
DOI: 10.1186/1741-7015-11-207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mediterranean diet on blood pressure in the PREDIMED trial: results from a randomized controlled trial

Abstract: BackgroundHypertension can be prevented by adopting healthy dietary patterns. Our aim was to assess the 4-year effect on blood pressure (BP) control of a randomized feeding trial promoting the traditional Mediterranean dietary pattern.MethodsThe PREDIMED primary prevention trial is a randomized, single-blinded, controlled trial conducted in Spanish primary healthcare centers. We recruited 7,447 men (aged 55 to 80 years) and women (aged 60 to 80 years) who had high risk for cardiovascular disease. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(173 citation statements)
references
References 25 publications
11
158
0
4
Order By: Relevance
“…Likewise, consumption of nuts was significantly inversely associated with hypertension (RR: 0.66; 95% CI: 0.44, 1.00; P = 0.049) in a recent meta-analysis of four prospective studies [12]. Dietary patterns such as the DASH diet [19], the Mediterranean diet [21] and the Nordic diet [41] have been shown to reduce BP. In our previous research, a meta-analysis of 17 randomized controlled trials showed that a dietary pattern that was rich in fruits, vegetables, wholegrains, legumes, nuts, seeds, dairy and fish and low in processed foods and red meat reduced SBP and DBP by 4.06 mmHg and 2.30 mmHg, respectively [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, consumption of nuts was significantly inversely associated with hypertension (RR: 0.66; 95% CI: 0.44, 1.00; P = 0.049) in a recent meta-analysis of four prospective studies [12]. Dietary patterns such as the DASH diet [19], the Mediterranean diet [21] and the Nordic diet [41] have been shown to reduce BP. In our previous research, a meta-analysis of 17 randomized controlled trials showed that a dietary pattern that was rich in fruits, vegetables, wholegrains, legumes, nuts, seeds, dairy and fish and low in processed foods and red meat reduced SBP and DBP by 4.06 mmHg and 2.30 mmHg, respectively [42].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary pattern analysis has been recommended in nutritional epidemiology as an additional method to better understand relationships between diet and chronic diseases [18]. Various beneficial dietary patterns for BP regulation include the DASH diet [19], the Nordic diet [20] and the Mediterranean diet [21]. These dietary patterns are characterized by a diet that is high in fruit and vegetables, whole grains, legumes, seeds and nuts, fish and dairy and has a low consumption of meat and sweets and moderate alcohol intake.…”
Section: Introductionmentioning
confidence: 99%
“…dietary-induced BP decreases that in turn will reduce the risk of adverse cardiovascular event (28).…”
Section: Significancementioning
confidence: 99%
“…§ Mixed nuts ¼ almonds, pistachios, walnuts, groundnuts, hazelnuts, pecans, cashews and macadamias. (52) (83) 4 years n 7158 (control ¼ 2064, OO ¼ 2345, nuts ¼ 2065), M and F, risk of CVD, mean 67 (SD 6) years (86) 4 weeks per arm fasting glucose or insulin (48,63 -76) . One study that failed to achieve an improvement in insulin sensitivity supplemented participants' diets with 100 g almonds/d for 4 weeks.…”
Section: Effects Of Nuts On Glucoregulationmentioning
confidence: 99%